ClickArr: a novel, high-throughput assay for evaluating β-arrestin isoform recruitment - Alexander R. French; Alexander R. French; Yazan J. Meqbil; Yazan J. Meqbil; Richard M. van Rijn; Richard M. van Rijn; Richard M. van Rijn (Frontiers Media S.A., 2023)
Background: Modern methods for quantifying signaling bias at G protein-coupled receptors (GPCRs) rely on using a single β-arrestin isoform. However, it is increasingly appreciated that the two β-arrestin isoforms have unique roles, requiring the ability to assess β-arrestin isoform preference. Thus, methods are needed to efficiently screen the recruitment of both β-arrestin isoforms as they compete for a target GPCR in cells.Methods: We used molecular cloning to develop fusion proteins of the δ-opioid receptor (δOR), β-arrestin 1, and β-arrestin 2 to fragments of click beetle green and click beetle red luciferases. In this assay architecture, recruitment of either β-arrestin 1 or 2 to the δOR generates a spectrally distinct bioluminescent signal, allowing us to co-transfect all three constructs into cells prior to agonist challenge.Results: We demonstrate that our new assay, named "ClickArr," is a live-cell assay that simultaneously reports the recruitment of both β-arrestin isoforms as they compete for interaction with the δOR. We further find that the partial δOR agonist TAN67 has a significant efficacy bias for β-arrestin 2 over β-arrestin 1 when recruitment is normalized to the reference agonist leu-enkephalin. We confirm that ClickArr reports this bias when run either as a high-throughput endpoint or high-throughput kinetic assay, and cross-validate this result using the PathHunter assay, an orthogonal commercial assay for reporting β-arrestin recruitment to the δOR.Conclusion: Our results suggest that agonist:GPCR complexes can have relative β-arrestin isoform bias, a novel signaling bias that may potentially open up a new dimension for drug development.